INHIBITION PROPERTIES OF CLINICALLY IMPORTANT ENZYMES IN WOUND HEALING BY BEE VENOM - Merve Keskin; Saban Keskin; Semiramis Karlidag (Journal of Animal and Plant Sciences, 2024)
Apitherapy has importance in traditional and complementary medicine practices, including applications made by directly or functionalizing honey, pollen, propolis, bee venom, and bee bread (perga) obtained from honey bee colonies. Bee venom is preferred by apitherapists and is directly applied to the body from the bee sting or used in crystalline form. Apitoxin is a product that is formed in the venom bag of bees and contains mainly apamin, melittin, MCD-peptide, hyaluronidase, histamine, and phospholipase A2. Due to its these active ingredients, bee venom is effective in arthritis, central and peripheral nervous system diseases, respiratory diseases, gastroenterology, cardiovascular system diseases, eye diseases, skin diseases, urology, endocrinology, cancer diseases, and using it in the cosmetics industry is very popular. Although bee venom is widely used directly or indirectly in apitherapy applications, it is not possible to use standardized bee venom as a drug. In this study, the amount of total protein, melittin, and phospholipase A2 amounts of bee venom samples were determined and their inhibition effects on collagenase and myeloperoxidase enzymes were examined. The mean amounts of phospholipase A2, apamin, and melittin contained in bee venom samples were found to be 46.38%±0.10%, 2.19±0.11%, and 12.46±0.19%, respectively. It was determined that bee venom samples inhibited the collagenase enzyme by more than 50%. It shows that bee venom has an inhibitory effect on clinically important enzymes. However, it is necessary to conduct allergy tests before the use of the bee venom directly.
Keywords: Apis mellifera L.; apitoxin; collagenase; myeloperoxidase; wound healing